The experience of and coping with an induced abortion: A rapid review - Roché Lyon; Karel Botha (AOSIS, 2021)
This rapid review was conducted to determine the scientific evidence available on how women experience induced abortion and how they cope with the subjective experience thereof. The aim of this review was to systematically explore and synthesise scientific evidence on how women experience and cope with induced abortion. The guidelines of the National Institute for Health and Clinical Excellence were used as a framework to review current international and national literature. The researchers made use of Ebsco Discovery Service to search for relevant studies. This was done by employing key concepts and related synonyms. Eleven relevant studies were identified. As the study was exploratory in nature, covering a relatively small selection of studies, heterogeneous in methodology and cultural focus, only a few general trends were highlighted. Not much information was found for women in the South African context. The study found that socio-economic disadvantages and premorbid relationships are important factors that should be better researched, understood and managed in a South African context. Despite many studies on how women experience and cope with induced abortion, the review revealed the need for research related to specific challenges and experiences of South African women.